STUDIES IN THE FLORA OF ARABIA: XXXI. NEW RECORDS FROM THE SULTANATE OF OMAN - Patzelt, A.; Harrison, T.; Knees, S. G.; Al Harthy, L. (Edinburgh Journal of Botany, 2014)
Sixty new or updated records of plant species are reported from the Sultanate of Oman, as a result of field work and herbarium research. Four taxa represent new records for Arabia, 26 are new records for Oman, and 30 represent an extended distribution within Oman. Some previously doubtful records are confirmed. Brief comments are given on the phytogeography and ecology of the taxa. Most new records have been made in mountainous areas, either in southern or northern Oman, mostly in areas that previously were botanically very poorly known or unexplored.